Octanoate in Human Albumin Preparations Is Detrimental to Mesenchymal Stromal Cell Culture - Way-Wua Wong; Andrew D. MacKenzie; Vicky J. Nelson; James M. Faed; Paul R. Turner (Hindawi Limited, 2015)
Cell therapies hold great promise as the next major advance in medical treatment. To enable safe, effective ex vivo culture whilst maintaining cell phenotype, growth media constituents must be carefully controlled. We have used a chemically defined mesenchymal stromal cell culture medium to investigate the influence of different preparations of human serum albumin. We examined two aspects of cell culture, growth rate as measured by population doubling time and colony forming ability which is a representative measure of the stemness of the cell population. Albumin preparations showed comparative differences in both of these criteria. Analysis of the albumin bound fatty acids also showed differences depending on the manufacturing procedure used. We demonstrated that octanoate, an additive used to stabilize albumin during pasteurization, slows growth and lowers colony forming ability during ex vivo culture. Further to this we also found the level of Na+/K+ ATPase, a membrane bound cation pump inhibited by octanoate, is increased in cells exposed to this compound. We conclude that the inclusion of human serum albumin in ex vivo growth media requires careful consideration of not only the source of albumin, but also the associated molecular cargo, for optimal cell growth and behavior.